Erratum to pre-operative use of aspirin in patients undergoing coronary artery bypass grafting: a systematic review and updated meta-analysis - Solo, Karla; Lavi, Shahar; Choudhury, Tawfiq; Martin, Janet; Nevis, Immaculate F.; Kwok, Chun Shing; Kotronias, Rafail A.; Nishina, Natsumi; Sponga, Sandro; Ayan, Diana; Tzemos, Nikolaos; Mamas, Mamas A.; et al. (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Erratum to: J Thorac Dis 2018;10:3444-59